PERLINDUNGAN HUKUM PATEN ASING YANG TELAH TERDAFTAR DI INDONESIA - Aureelia Djafar (Jurnal Dialektika Hukum, 2022)
THE PROTECTION OF FOREIGN PATENTS BASED IN INDONESIA The establishment of Law number 14 of 2001 concerning Patentas a follow up policy after the ratification of the World Trade Organization (WTO) including its attachment concerning Trade Related Intellectual Property Rights (TRIPs) has brought legal consequence. That is to apply The TRIPs agreement in nationallaw where one of the principle is known the National principletoward foreign patents in Indonesia. Patent is one of the scopeof intellectual property rights. A patent is granted to a person or a group of people its discovery in the field of technologywhich has a very important position and strategically tosupport. A patent is an exclusive right granted by the State tothe inventor's top invensinya in the field of technology and thepeople who got the rights to it. The patent is necessary tosupport the variety of life in the community. The foreign Patentrights will be preserved as long as the invention has registeredto directorate-general of Intellectual Property Rights of theRepublic of Indonesia. The invention registration could beapplied in 2 (two) mechanism i.e. priority right registration andPatent Cooperation Treaty (PCT) and the application must beauthorized by Indonesian IPR consultant. Patent Law No. 13 year 2016 do not only provide protection against patent citizensof Indonesia but also provides protection against patent lawforeign citizens in Indonesia. The protection of the law wasgiven in order to increase investment in Indonesia and wouldenhance inventor's top invention useful for developments in society. To give a sense of security, convenient to the Inventor'sforeign country then provide protection. All countries need toratify them to protect the IPR of their citizens at theinternational level. This research concerns with thearrangement and implementation of patent protection throughPCT and RUP. This research concludes that the internationalconventions have been made to accommodate and guaranteethe legal aspect of the Treaty, such as Trips, PCT and WIPO. As a country which has ratified the Treaty, Indonesia has issuedPresidential Decree No. 16 of 1997 which is finalized into Law No. 13 of 2016 on Patents (Article 33), stating that applicationsmay be filed under a Patent Cooperation Treaty. This researchalso points out that although it’s believed that all countries willbenefit from PCT and RUP, PCT has not attracted significantnumbers of applicants. That means, there is still much work tobe done in invention patenting law foreign citizens in Indonesia. Keywords : legal protection, patents, foreign patent.